The Effectiveness of aDrug Abuse Prevention Module Based on Self-Assertiveness, Spirituality and Belief in the Detriments of Drug Abuse (MPDASK) - Amin Al Haadi Shafie; Durrah Athirah Walid; Abdul Rashid Bin Abdul Aziz; Nurhafizah Mohamad Yassin; Dini Farhana Bt Baharudin; Khatijah Othman; Rafidah Aga Bt Mohd Jaladin; Salleh Amat; Suzaily Wahab (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2024)
VOL. 6 NO. 2